THE IMPLEMENTATION OF BABY-FRIENDLY COMMUNITY INITIATIVE ON KENYA AND INDONESIA - Muhka, Reni; Huriah, Titih (Universitas Aisyah Pringsewu, 2024)
Baby Friendly Community Initiative (BFCI) is one of the programs to improve the quality of care for mothers and babies in the community. One of BFCI's flagship programs is exclusive breastfeeding. This Literature Review aims to determine the implementation of BFCI programs in developing countries. The Literature Review follows PRISMA's reporting method. The database uses Science Direct, PubMed, Scopus, EBSCO and Google Scholar. The keyword uses